The Role of MSMEs in Driving Economic Growth and Income Equality in Indonesia: PERAN UMKM DALAM MENDORONG PERTUMBUHAN EKONOMI DAN PEMERATAAN PENDAPATAN DI INDONESIA - Khumairo, Hazmatul; Hersiyah; Mashudi (Green Engineering Society, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in driving national economic growth and income distribution in Indonesia. As a sector that absorbs more than 97% of the national workforce and contributes significantly to Gross Domestic Product (GDP), MSMEs are an important pillar in strengthening the economic foundation of the people. The existence of MSMEs is able to create new jobs, reduce social disparities, and expand economic access to various levels of society, especially in remote areas. Amid the challenges of globalization and the development of technology, MSMEs have shown high resilience in maintaining economic stability, especially during crises. However, there are still various challenges that must be overcome, such as access to capital, digitalization, and improving the quality of human resources. Support from the government through affirmative policies, training, and facilitation of market access is key to encourage further empowerment of MSMEs. By optimizing the role of MSMEs, Indonesia does not only accelerate national economic growth, but also ensures the creation of a more equitable and sustainable income distribution across all regions.